2000
DOI: 10.1039/b003968n
|View full text |Cite
|
Sign up to set email alerts
|

NMR diffusion spectroscopy for the characterization of multicomponent hydrogen-bonded assemblies in solution

Abstract: NMR diffusion measurements on 10 different multicomponent hydrogen-bonded assemblies, viz. the three single rosettes SR1-SR3 (1 3 ؒ2a 3 , 1 3 ؒ2b 3 , 1 3 ؒ2c 3 ) the double rosettes DR1-DR5 (3a 3 ؒ2a 6 , 3b 3 ؒ2b 6 , 3c 3 ؒ2a 6 , 3d 3 ؒ2a 6 , 3e 3 ؒ2a 6 ), and DR6 (4a 3 ؒ1 6 ), and the tetrarosette TR (5 3 ؒ2a 12 ) are described. Some of the above rosettes have been previously identified as well-defined assemblies (viz. SR1, DR1-DR3, and TR) using established characterization techniques ( 1 H NMR spectroscopy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 39 publications
4
69
0
3
Order By: Relevance
“…Considering the known crystal structure of the corresponding double rosette assemblies (21) and the gas phase minimized structure of the tetrarosettes (see Scheme 1; ref. 22), the observed nanorods can be concluded to consist of rows of tetrarosette assemblies. Based on the gas phase minimized structure, the area requirement for such an arrangement is Ϸ8.6-9.9 nm 2 , depending on the orientation.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the known crystal structure of the corresponding double rosette assemblies (21) and the gas phase minimized structure of the tetrarosettes (see Scheme 1; ref. 22), the observed nanorods can be concluded to consist of rows of tetrarosette assemblies. Based on the gas phase minimized structure, the area requirement for such an arrangement is Ϸ8.6-9.9 nm 2 , depending on the orientation.…”
Section: Resultsmentioning
confidence: 99%
“…[84,85] The pulsed gradient spin echo (PGSE) sequence was used to characterize several rosettes prepared by the research group of Reinhoudt. [86] In this study, single, double, and tetrarosettes of the type shown in Scheme 1 were classified on the basis of their diffusion coefficients. [86] Relatively good agreement was found between the hydrodynamic diameter extracted from diffusion NMR measurements and those obtained from gas-phase-minimized structures.…”
Section: Molecular Size and Shapementioning
confidence: 99%
“…Furthermore, diffusion ordered NMR spectroscopy (DOSY) of an analogous mixture showed the formation of a single slow diffusing species, rather than a mixture of oligomers with different diffusion coefficients. Using the diffusion coefficient of monomeric TIPDS--dA and its molecular weight as references, a molecular weight range for the species in the mixture can be estimated and is consistent with a hexameric rosette 48 .…”
Section: Investigation Of Fiber Structurementioning
confidence: 99%